Freiform-Optiken im Nahfeld von LEDs - Wendel, Simon (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2014)
This thesis analyzes the process of designing compact and efficient non-imaging optical systems for general lighting. The main focus is on automated methods for the design of freeform-optics for light emitting diodes (LEDs). As an essential result, the development of the method OFFD (optimization with freeform deformation) proves to be a fast and flexible way to design optics for numerous applications.